2019
DOI: 10.3174/ajnr.a6067
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic and Pathologic Features of the Transmantle Sign in Focal Cortical Dysplasia: The T1 Signal Is Useful for Differentiating Subtypes

Abstract: BACKGROUND AND PURPOSE: The transmantle sign is a characteristic MR imaging finding often seen in focal cortical dysplasia type IIb. The transmantle sign is typically hyperintense on T2WI and FLAIR and hypointense on T1WI. However, in some cases, it shows T1 high signal. We evaluated the imaging and pathologic findings to identify the causes of the T1 high signal in the transmantle sign. MATERIALS AND METHODS: We retrospectively reviewed the preoperative imaging data of 141 consecutive patients with histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Kimura et al 18 reported that T1 hyperintensity of the transmantle sign of FCD type IIb is associated with the high density of balloon cells, independent of the density of dysmorphic neurons, the severity of gliosis, and calcifications. In a study by Kusama et al, 19 T1WI-CHESS detected the transmantle sign of FCD type IIb as marked hyperintensity where numerous balloon cells were located in a resected specimen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kimura et al 18 reported that T1 hyperintensity of the transmantle sign of FCD type IIb is associated with the high density of balloon cells, independent of the density of dysmorphic neurons, the severity of gliosis, and calcifications. In a study by Kusama et al, 19 T1WI-CHESS detected the transmantle sign of FCD type IIb as marked hyperintensity where numerous balloon cells were located in a resected specimen.…”
Section: Discussionmentioning
confidence: 99%
“…However, our present findings were consistent with the radiology-pathology correlation in FCD type IIb. 18 Further radiology-pathology correlation studies are also needed for TSC. A third limitation is that the ages of the patients varied, including patients whose myelination is ongoing and those with completed myelination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed qualitative MRI indicators were as follows: cortex thickening, gray-white matter blurring, transmantle sign, and signal intensity changes of both the gray and white matter. The definition of the transmantle sign was “a markedly hyperintense funnel-shaped subcortical zone tapering toward the lateral ventricle” ( 15 ). The MRI-negative was defined as the invisible abnormal signals of the cortical or subcortical part.…”
Section: Methodsmentioning
confidence: 99%
“…More recently a study by Kumura et al revealed that T1-weighted hyperintense transmantle sign is associated with higher density of balloon cells without significant differences in the number of dysmorphic neurons or the severity of gliosis ( Fig. 10.9) [16]. Identifying a T1 hyperintense transmantle sign may have clinical relevance.…”
Section: Mesial Temporal Lobe/hippocampal Sclerosismentioning
confidence: 99%